Politics and political theater: the Dimensions and Apropriations of Political Thought in Scenic Production - Wey (UFRRJ), Beatriz (Instituto de Ciências Sociais da Universidade de Brasília, 2014)
The diversity of theoretical paradigms in the history of political thought reveals differing interpretations of social relations. There is no exact result for each reality comprehension. Instead, each model is a paradigm for the formulation of new theories that have a specific look in describing the empirical world. Theories create propositions about what should exist and so they fertilize the art world. Thus, theories gain a new perspective, a new look, the artist’s look, the playwright’s and director’s. Over time, political theory and art are responsible for new ways of thinking and acting political, in a perspective or another. In this article, we discuss how theater and political theory are juxtaposed and how theater includes political thought, by understanding politics as conflict and violence or politics as consensus and freedom. By appropriatingpolitic theories, theater can reveal its bigger or smaller political character.